Inklusi Global: Pemberdayaan Keterampilan Membatik dan Edukasi Mitigasi Kegawatdaruratan bagi Peserta Didik Disabilitas di LKP Aora Wistara Surabaya - Elga Ceisaria Andani; Ainun Ganisia; Rakhmalia Imeldawati; Nurul Fathiyyah; Putri Gunawan; Angel Erbabley (Rena Cipta Mandiri, 2026)
LKP Aora Wistara is a training institution for students with disabilities in Surabaya focusing on economic independence through the art of batik, yet it still faces challenges in environmental safety literacy. This community service activity aims to empower disabled students through the integration of vocational skills and emergency mitigation education. The method employed was an inclusive participatory approach involving strategic coordination, digital application-based emergency training, and batik mentoring themed